Haemoglobin Lepore Boston-Washington in Sicily: clinical, haematological, and biosynthetic studies. Issue 3 (June 1980) - Schiliro, G; Musumeci, S; Pizzarelli, G; Fischer, A; Romero, M A; Russo, G
Abstract : In the south-east of Sicily 23 children from 14 unrelated families have been diagnosed as suffering from haemoglobin Lepore. Such a high incidence shows that Sicily is an important focus of haemoglobin Lepore. The results of haematological and biosynthetic studies in 18 carriers of Hb Lepore and in five double heterozygotes for Hb Lepore and beta-thalassaemia are presented. In the carriers the haematological and biosynthetic data are compared with carriers of beta-thalassaemia, while the five double heterozygotes are compared with beta o- and beta +-thalassaemia major subjects. In the carriers of Hb Lepore no synthesis of delta beta-chains was observed in peripheral blood cells; in fact we found a peak in the bone marrow. Double heterozygotes with circulating nucleated red cells showed delta beta-chain synthesis in peripheral blood.